Strategi Peningkatan Kompetensi Tenaga Pendidik Melalui Komunitas Belajar Sekolah Di Sekolah Dasar Penajam Paser Utara Kalimantan Timur - Ibrahim Jamal, Dian; Hamid, Mulyadi; Muin, Sri Adrianti (Jurnal Online Manajemen ELPEI, 2025)
This research aims to measure the increase in the competency of teaching staff through school learning communities in North Penajam Paser Regency, East Kalimantan Province. This research was carried out at eight elementary schools in North Penajam Paser Regency, namely: SDN 009 Babulu, SDN 022 Babulu, SDN 023 Babulu, SD Muhammadiyah Babulu, SDN 003 Waru, SDN 006 Waru, SDN 009 Waru and SDN 011 Babulu. Data collection for this qualitative research was carried out using questionnaires from 8 school principals and 8 teachers as respondents. The results of the questionnaire that were returned and valid were 16 people. Data processing uses descriptive analysis from the results of observations and FGD in learning communities. What was discussed and the data obtained were supporting factors for increasing the competence of teaching staff and learning community activity strategies as a solution for increasing the competence of teaching staff. Qualitative data analysis is interview data selected and classified based on the interviewee's answers to interview questions in accordance with structural coding or guidelines that have been created by the researcher. The results of this research conclude that there are several supporting factors for increasing the competence of teaching staff and through learning community activity strategies as a solution to increasing the competence of teaching staff in elementary schools in North Penajam Paser Regency, East Kalimantan.